(untitled) (Bioscience Journal, 2020)
A sensitive and reliable process was established using high-performance liquid chromatography (HPLC) to distinguish conventional varieties of glyphosate-resistant genetically modified crops via shikimate detection in soybean (Glycine max L. Merril) seeds. Glyphosate has a well-defined mechanism of action. It is the only herbicide that specifically inhibits 5-enolpiruvilshikimate-3-phosphate synthase (EPSPS E.C. 2.5.1.19), which catalyzes the condensation of shikimate with phosphoenolpyruvate. This study is based on the concept that shikimate significantly accumulates in soybean plant tissues after EPSPS inhibition by glyphosate. In plants not subjected to glyphosate, shikimate is not easily detected because it quickly metabolizes into shikimate 3-phosphate and subsequently into 5-enolpiruvilshikimate 3-phosphate through the action of EPSPS. Conversely, in non-genetically modified plants subjected to glyphosate, shikimate metabolism is impaired, resulting in its accumulation. This metabolite can be detected in extremely low quantities (in the microgram range), through HPLC. In this study, six different contrasts were analyzed, each being formed by a transgenic cultivation and its parental strain, subject or not subject to the treatment of soaking with a 0.6% glyphosate solution. Chromatographic analyses indicated shikimate accumulation only in conventional cultivars with seeds previously soaked in a 0.6% glyphosate solution. Thus, this shikimate detection method can be used as a rapid and accurate means to distinguish soybeans with glyphosate-resistant qualities.